PENGEMBANGAN UMKM DARI PERSPEKTIF PENGEMBANGAN TEKNOLOGI INFORMASI AKUNTANSI - I Putu Mega Juli Semara Putra; I Dewa Made Endiana; Siluh Putu Natha Primadewi; Ni Kadek Dwi Rusjayanthi (KRISNA: Kumpulan Riset Akuntansi, 2019)
The Export Product Development Program (PPPE) is carried out on the Diva Lamp in Banjar Sapat, Tegalalang Village, Gianyar Regency and OMG Lamp located in Banjar Gentong, Tegalalang Village, Gianyar Regency. The craft products produced are room dividers, which are various types of room and interior partitions made from natural materials. The targeted output includes planning the separation of production space and product storefront space because in the production room, laying out facilities such as machines and work equipment is more permanent while the product storefront is more neatly arranged so that it creates a representative atmosphere for the customer. larger output with the same or fewer costs, smaller man hours, and or reduced machine working hours. Procurement is expected to reduce production prices and the length of time for completion of products so that the products produced can compete in the market. Improvements in terms of management, bookkeeping and marketing are carried out with the aim that administratively the operation of MSMEs can be more neatly organized so that it is easier in the process of planning, supervision and decision making. In terms of marketing, it is expected to add to the marketing model so that market share can be absorbed more optimally.